(3GdETQGa Ydi ePGgH GdCTQGas - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s ((3eMeO Hf CMeO Hf eMeO Gdecfi TYdGf s)
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3ef jQO Gddg Hg NjQG jabg aiGdOjf cJGH GdWgGQI (B: (3CLeYhG Ydi Cf GdUdGI dG JUM EdG HWgGQI EPG hLO GdSHjd EdjgG s
(3BNQgG (B:s
(3hGNJdahG ajeG EPG bJdJ Ce GdhdO SjOgG agPG ajeG JQGg ebfY Ef TGA Gddg hGddg SHMGfg hJYGdi GdeMehO Ydi Cf hab cPdc s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3CUhd Gdabgs